White Antiracism in Southern Ontario: Frames, Praxis and Awareness - Traoré, Ismaël (My University, 2017)
There has been an increase in reactionary racial violence in the past eight years following the presidency of Barack Obama, and in response to perceived threats to the racial and cultural order posed by movements for racial justice and the refugee crisis. Complicit to the spate of organized racial violence are passive white bystanders, who, through their inaction, have tolerated and given free reign to a resurgence of racial violence. Only a minority of whites have responded to calls for solidarity from Black, Indigenous and People of Color (BIPOC). This study set out to uncover how these minority of whites respond to racism. Drawing on narratives and questionnaires of thirty-eight white persons, I begin with an exploration of the frames that shape participants’ understanding of antiracism. Three frames are discussed: the (a) equality and human rights frame, (b) anti-oppression frame, and (c) whiteness-centered frame. The core of this study is on antiracism praxis. I discuss two categories of praxis: quotidian antiracism and organizational antiracism. In the former category are three types of antiracism strategies: (a) confrontation, (b) counterclaiming, and (c) covert and clandestine antiracism. The latter category consists of equality and equity focused strategies in education that I distinguish based on setting: (a) classroom antiracism and (b) administrative antiracism. This discussion is enriched by an investigation of the enablers and obstacles of antiracism and what respondents consider when deciding to engage in bystander action. In conversation with Frankenberg’s (1993) ‘race-cognizance’ concept, I present a subsidiary antiracism awareness that I call self-implication cognizance. I detail five ways participants stop themselves from ‘racing to innocence’ by implicating themselves in the hegemonic order of whiteness. This study contributes a typological model of frames and praxis and a situated picture of enablers of antiracism to the scholarship of white antiracism. It also offers insights for progressive whites and organizations interested in racial justice, equality and equity. Subject keywords: antiracism, activism, whiteness, white racial identity, racial awareness, frames, enablers, obstacles, racism
Keywords: White antiracism; Activism; White racial identity; Whiteness; Hamilton, Ontario, Canada; Frames; Praxis; Action; Strategies; Racial awareness; Enablers; Obstacles; Racism